2020
DOI: 10.1007/s11051-020-04990-9
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen-loaded PLA/DPPE-PEG lipid-polymeric nanocapsules for inhibiting the growth of estrogen-positive human breast cancer cells through cell cycle arrest

Abstract: The strategy of drug encapsulation with biocompatible polymeric nanocapsules could be a promising approach to improve the delivery of poorly water-soluble drugs for cancer therapy. The aim of this study was to investigate the drug delivery of tamoxifen from biocompatible nanocapsules made of poly (D,L-lactide) (PLA) c o r e a n d 1 , 2 -d i p a l m i t o y l -s n -g l y c e r o -3phosphoethanolamine-N-[methoxy(polyethyleneglycol)-2000] (DPPE-PEG) shell in the treatment of breast cancer.The analytical technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 77 publications
2
8
0
Order By: Relevance
“…Therefore, the loaded TMXs on the FAconjugated GQDs nanocarriers were entered into MCF-7 cells with endocytosis via the folate receptor and TMX release process of TMX-FPG exhibited the controlled release behavior similar to the previous reports [42]. A comparison between the results of the present study and our ndings in the previous study showed that the toxicity of loaded TMX on FPGs was approximately 1.84 times higher than that of loaded TMX on PLA/DPPE-PEG lipid polymeric nano-capsules [43]. In addition, TMX-FPG showed 2.4 times more toxicity in the same exposure time on MCF-7 cells than loaded TMX on gelatin [44].…”
Section: In Vitro Cell Viability Analysissupporting
confidence: 90%
“…Therefore, the loaded TMXs on the FAconjugated GQDs nanocarriers were entered into MCF-7 cells with endocytosis via the folate receptor and TMX release process of TMX-FPG exhibited the controlled release behavior similar to the previous reports [42]. A comparison between the results of the present study and our ndings in the previous study showed that the toxicity of loaded TMX on FPGs was approximately 1.84 times higher than that of loaded TMX on PLA/DPPE-PEG lipid polymeric nano-capsules [43]. In addition, TMX-FPG showed 2.4 times more toxicity in the same exposure time on MCF-7 cells than loaded TMX on gelatin [44].…”
Section: In Vitro Cell Viability Analysissupporting
confidence: 90%
“…Additionally, the bands at 1735.52 cm −1 , 1582.84 cm −1 , and 1498.18 cm −1 were because of carboxylic C=O, aromatic C–C, and C=C ring stretching, respectively. Absorptions at 1299.47 cm −1 , 1235.25 cm −1 , and 1122.88 cm −1 were because of aromatic C–O stretching [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the use of lower TMX doses utilizing nano-based drug delivery systems can be beneficial to reducing drug toxicity and providing more efficient drug distribution [30] . For nano-carrier systems, drug loading efficiency is a significant parameter, especially for hydrophobic drugs with common side effects [31] . To reveal the potential of the Fe 3 O 4 -DPN-HA-FA NPs for the delivery of controlled TMX, the loading capacity and in vitro release amount were calculated.…”
Section: Loading Capacities and Release Amountsmentioning
confidence: 99%